Bioethics and health care (Revista Iberoamericana de Bioética, 2016)
The relationship with health has changed in recent decades. It has become more social field and more people are involved (doctors, nurses, psychologists, social workers, etc.), leading to a rethink of the relationship in terms of ethics. The fact that deliberative and narrative models can sufficiently help to solve ethical conflicts has been acknowledged. It explores the institutional universe in which the relationship develops. It recognizes the difficulty of the multidisciplinary and Multiprofessional work, as well as the role change of nursing, going from a care-based model to a process-based model. It proposes a collaborative way of working with the patient and his or her family.
Keywords: Health relationship; deliberative ethics; team work; nursing; medicine.